2008
DOI: 10.1149/1.2903882
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effect of Graphite Degradation on Irreversible Capacity in Lithium-ion Cells

Abstract: The effect of surface structural damage on graphitic anodes, commonly observed in tested Li-ion cells, was investigated. Similar surface structural disorder was artificially induced in Mag-10 synthetic graphite anodes using argon-ion sputtering. Raman microscopy, scanning electron microscopy (SEM) and Brunauer Emmett Teller (BET) measurements confirmed that Ar-ion sputtered Mag-10 electrodes display similar degree of surface degradation as the anodes from tested Li-ion cells. Artificially modified Mag-10 anode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 49 publications
(75 reference statements)
2
51
0
Order By: Relevance
“…Additionally, this result is also support a view reported by Hardwick et al [22].They have shown that the surface disordering of the graphite may lead to the continuous reformation of SEI, resulting in a thicker SEI layer, and consequently higher interfacial resistance, as supported by our EIS data, and great consumption of active lithium [23].…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, this result is also support a view reported by Hardwick et al [22].They have shown that the surface disordering of the graphite may lead to the continuous reformation of SEI, resulting in a thicker SEI layer, and consequently higher interfacial resistance, as supported by our EIS data, and great consumption of active lithium [23].…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…three factors: ionic conductivity of the electrolyte, the charge transfer resistance between the active material and the electrolyte, and the double-layer capacitance [15][16][17][18][19]. It is can be clearly seen that R ct is increased with increase of temperature, which is due to the increase of interfacial resistance induced by the thicker SEI layer on the surface of graphite anode [20,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though considered fairly stable due to the moderate dimensional changes upon Li-intercalation compared to the potential metallic anode materials [1][2][3], structural degradation of graphitic carbon based anodes still contribute considerably towards the overall capacity fade of Li-ion batteries [4][5][6][7][8][9]. In fact, such structural degradation is possibly one of the major contributing factors towards the aging of Li-ion batteries because it leads to the continued formation of solid electrolyte interphase (SEI) layers at the 'freshly formed' graphitic carbon surfaces, which http://dx.doi.org/10.1016/j.carbon.2015.02.078 0008-6223/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…During charge/discharge cycling or storage of LIBs, aging effects may occur [7]. Mechanical degradation like graphite exfoliation or surface structural disordering leads to loss of mobile lithium or self-discharge [8][9][10][11]. One of the main reasons for exfoliation is the cointercalation of solvated lithium ions.…”
Section: Introductionmentioning
confidence: 99%